Bentuk dan Implementasi Nilai Pendidikan Karakter dalam Cerita Mitos Manarmakeri Suku Biak Numfor Provinsi Papua - Dimara, Flora Hana (Melanesia : Jurnal Ilmiah Kajian Bahasa dan Sastra, 2017)
This study aims to reveal the value of character education in the Story of Myth Manarmakeri (CMM) Biak Numfor Papua Tribe. This study also presents a description of the life and social reality of the Biak Numfor Tribe of Papua. As a source of local Papuan literary development, CMM is intended as a medium to foster intelligence, love, and respect for local literature as part of the ancestral heritage. Thus, CMM is useful in supporting cultural knowledge, developing feelings of intention, and forming character or character. Literature part of literary local, CMM is considered able to form the character of students effectively because the values and morals contained in the literary works are not delivered directly, but through stories and metaphors so that the educational process is fun and not patronizing. The values contained in the literary works are pervaded by the students and unconsciously reconstruct their attitudes and personality.The value of character education in CMM Biak Numfor Papua tribe can be decomposed through analysis, namely (1) form of character education value, and (2) implementation of character education value.